Development of Puzzle Media in Science Learning on Animal Life Metamorphosis Material for Grade III SDN 07 Koto Baru - Yulia Darniyanti; Ahmad Ilham Asmaryadi; Nur Annisa (The Future of Education Journal, 2025)
This research is motivated by the problem of students who are less enthusiastic in following the learning process, in the learning process students feel bored and play alone so that they pay less attention to learning and the lack of interesting learning media so that students often feel bored during the learning process. To overcome this, the author tries to develop teaching materials in the form of puzzle learning media with the aim of helping students understand learning materials, especially animal metamorphosis material, adding to the learning media available in schools and producing the development of valid, practical, and effective puzzle media in grade III elementary schools so that it can increase students' interest in learning at SDN 07 Koto Baru. The type of research is research and development (R&D) which uses the ADDIE development model consisting of the analysis stage, the analysis includes material analysis, student needs analysis, and student characteristics analysis. The design stage is the design of the Puzzle learning media, namely the instrument design and framework design. The development stage is the development stage is a validation test. The implementation stage is the implementation stage is carried out for practicality and effectiveness. The evaluation stage is carried out at each stage starting from analysis, design, development, and implementation. that the validity results that have been carried out by the material feasibility validator with an average value percentage of 90% are categorized as very valid, the teaching module feasibility validator with an average value percentage of 97.2% is categorized as very valid, the graphic feasibility validator with an average value percentage of 93.5%, and the language feasibility validator with an average value percentage of 88.1% are categorized as very valid. Thus, the results of the Puzzle Media validity assessment that have been designed by researchers have been averaged with a percentage of 92.1% categorized as very valid, the results of practicality with an average score of 98.7% are categorized as very practical, meaning that puzzle media can be used easily for the learning process while the results of effectiveness with a score of 82.3% are categorized as very practical, meaning that the application can increase students' interest in learning.